2012
DOI: 10.5152/akd.2012.127
|View full text |Cite
|
Sign up to set email alerts
|

Normal values correlates of carotid intima- media thickness and affecting parameters in healthy adults

Abstract: ÖZETAmaç: Karotis arter intima-media kalınlık (KİMK) değişiklikleri ile aterosklerotik sürecin başlangıcını erken dönemde ortaya koymak mümkün-dür. Türk toplumunda normal bireylerin KİMK'ları incelenmemiştir. Bu çalışmada ateroskleroz yönünden risk faktörleri olmayan normal bireylerde KİMK ve etkileyen parametrelerin incelenmesi amaçlandı. ABSTRACTObjective: Early changes in atherosclerosis can be diagnosed by the carotid artery intima-media thickness (CIMT) measurement. Normal range of CIMT in healthy subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
0
16
3
Order By: Relevance
“…An increase in CIMT with each decade of age (0.066 cm/decade) was observed, with CIMT values as high as 0.0733 cm in the 70-79 years group (44). An increase of 0.1 mm in CIMT is known to raise the risk of myocardial infarction by 11% (45).…”
Section: Discussionmentioning
confidence: 96%
“…An increase in CIMT with each decade of age (0.066 cm/decade) was observed, with CIMT values as high as 0.0733 cm in the 70-79 years group (44). An increase of 0.1 mm in CIMT is known to raise the risk of myocardial infarction by 11% (45).…”
Section: Discussionmentioning
confidence: 96%
“…Nitric oxide (NO) is responsible for trigeminovascular inflammation during migraine attacks (14). During migraine, endothelial NO and superoxide anions increase in the cerebral blood flow (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…CCA-IMT, a structural marker of early atherosclerosis was increased in migraineurs, this elevation with patients and controls was excluded. According to a large-scale study on the same race performed in 2012, the CCA-IMT normal value was 0.458±0.116 mm in males and 0.47±0.104 mm in females (15).…”
Section: Usg Methods (Carotid Intima Thickness)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the observational cohort study conducted by Beşir et al in 2010 in Turkey, it was found that CIMT values in healthy volunteers increased only by age and it has been found that CIMT measurement can be used to evaluate early atherosclerosis burden in adult individuals [14]. Recent studies have shown that the risk of ischaemic stroke is high in patients with migraine, especially in women with migraine with aura [15,16].…”
Section: Discussionmentioning
confidence: 99%